Quantifying nursing care delivered in Kenyan newborn units: protocol for a cross-sectional direct observational study - Gathara, David (BMJ Open, 2018)
INTRODUCTION: In many African countries, including Kenya, a major barrier to achieving child survival goals is the slow decline in neonatal mortality that now represents 45% of the under-5 mortality. In newborn care, nurses are the primary caregivers in newborn settings and are essential in the delivery of safe and effective care. However, due to high patient workloads and limited resources, nurses may often consciously or unconsciously prioritise the care they provide resulting in some tasks being left undone or partially done (missed care). Missed care has been associated with poor patient outcomes in high-income countries. However, missed care, examined by direct observation, has not previously been the subject of research in low/middle-income countries. METHODS AND ANALYSIS: The aim of this study is to quantify essential neonatal nursing care provided to newborns within newborn units. We will undertake a cross-sectional study using direct observational methods within newborn units in six health facilities in Nairobi City County across the public, private-for-profit and private-not-for-profit sectors. A total of 216 newborns will be observed between 1 September 2017 and 30 May 2018. Stratified random sampling will be used to select random 12-hour observation periods while purposive sampling will be used to identify newborns for direct observation. We will report the overall prevalence of care left undone, the common tasks that are left undone and describe any sharing of tasks with people not formally qualified to provide care. ETHICS AND DISSEMINATION: Ethical approval for this study has been granted by the Kenya Medical Research Institute Scientific and Ethics Review Unit. Written informed consent will be sought from mothers and nurses. Findings from this work will be shared with the participating hospitals, an expert advisory group that comprises members involved in policy-making and more widely to the international community through conferences and peer-reviewed journals.